Country Partnership Framework for the Republic of Kazakhstan for the Period 2020-2025 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Kazakhstan, 2020)
Past economic success notwithstanding, this Country Partnership Framework (CPF) comes at a time when Kazakhstan faces growing challenges. Institutional and governance reforms have been identified by the Systematic Country Diagnostic (SCD) as the main constraint to achieving Kazakhstan's development goals. This CPF incorporates shifts in the World Bank Group (WBG) program that are intended to directly support Kazakhstan's development objectives and assist it in IBRD graduation. The CPF will also involve a high degree of selectivity to ensure that its programming is consistent with the WBG's value proposition to upper-middle-income countries as well as the IBRD graduation policy.